Mechanical, microstructure and reaction process of calcium carbide slag-waste red brick powder based alkali-activated materials (CWAAMs). (10th January 2022) - Cong, Peiliang; Cheng, Yaqian; Ge, Wanshuai; Zhang, Anyu
Abstract: The paper attends to the utilization and performance improvement of waste red brick powder activated by calcium carbide slag (CCR). Therefore, the improvement of mechanical properties and microstructure of calcium carbide slag-waste red brick powder based alkali-activated materials (CWAAMs) by silica fume, composite activator and curing temperature was explored. Compressive strength tests, reaction process and microstructural analysis were performed including Fourier transform infrared, X-ray diffraction, scanning electron microscope-energy dispersive X-ray spectroscopy and thermogravimetry. The results showed that the compressive strength of CWAAMs increases by 8 times that of CWAAMs without silica fume, resulting from that silica fume increased the stacking speed and yield of C-S-H gel, making the structure of CWAAMs compact. Through the microscopic analysis of the reaction products in the reaction process, it is found that high alkali concentration and high-temperature curing conditions can promote the alkali-activated reaction to proceed faster. Furthermore, the 28d compressive strength of the CWAAMs reached 46.70 MPa curing at 100 °C for 1 d. Because the high concentration of Ca 2+ and Na +  ions of the composite activator (CCR and NaOH solution) may produce synergistic effect curing at high temperature, forming massive C-S-H and (C, N)-A-S-H gel to fill the space between the particles, thus forming a more compact paste structure. Graphical abstract: Image 1 Highlights: The silica fume can improve the microstructure and mechanical properties of the CWAAMs. Calcium carbide slag or mixture with NaOH solution were used as alkali activators. High-temperature curing can significantly improve the properties of the CWAAMs. The reaction process of CWAAMs under different conditions was also studied.